Respuesta :

Answer:

Step-by-step explanation:

Use distributive property: a*(b+c) =a*b +a*c

1) 785 * 105 = 785 * (100 + 5)

                  = 785*100 + 785*5

                  = 78500 + 3925

                  = 82425

~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~

2) 1006 * 95 = (1000 + 6) *95

                     = 1000*95 + 6*95

                      = 95000 + 570

                     = 95570

~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~

3) 3096*91  = 3096 * (100 - 9)

                    = 3096*100 - 3096*9

                    = 309600 - 27864

                    = 281736